Characteristics of VLF Saucers and Auroral Hisses from ISIS Satellites Received at Syowa Station, Antarctica - Ondoh, Tadanori; Nakamura, Yoshikatsu; Murakami, Toshimitsu (1981)
P(論文) Properties of VLF saucers and auroral hisses have been studied by using ISIS VLF electric field data (50Hz-30kHz) received at Syowa Station, Antarctica. Source altitudes of VLF saucers are obtained from frequency-time spectra of VLF saucers by assuming the limiting ray model. The source distances of VLF saucers are less than about 800km below the satellite. VLF saucers occur around the high-and low-latitude ends of the auroral hiss region. The active auroral hiss and the stable auroral hiss are classified according to the variability of the narrow-band intensity data processed from ISIS VLF tapes. The frequent occurrence region of the former agrees well with the usual auroral zone, while the latter occurs at invariant latitude from about 70°to about 80°both on the day and night sides. The properties of the stable auroral hiss have some similarities to those of the precipitating low-energy electrons, the so-called polar rain, in occurrence region and in intensity. The narrow-band 5kHz hiss occurs often at invariant latitudes of 61°±5°, which are close to the average plasmapause latitude, during the daytime and nighttime. departmental bulletin paper